Depression, Self-Esteem and Sociodemographic Determinants of Suicidal Ideation Among University Undergraduates - Akanni, Abimbola A.; Oduaran, Choja A. (Journal of Reviews on Global Economics, 2019)
The study examined the direct effects and interaction effects of depression, self-esteem, age and religious affiliation on suicidal ideation. A total of 241 (Mean age=18.89; female=52.7%) university undergraduates in a Nigerian university that were selected through convenient sampling procedure responded to the Rosenberg Self-Esteem Scale, Beck Depression Scale (Short form) and Suicidal Ideation Questionnaire. Results of the Two-Way ANOVA revealed a between subject significant main effect of depression, (F = 11.27, p<.05, Æžp2 = .089) and a non-significant main effects of self-esteem, (F= 1.82, p>.05, Æžp2 = .015) on suicidal ideation. The interaction effect was not found to be significant (F= .49, p<.05, Æžp2 = .008). however, age (F = 8.06, p<.01, Æžp2 = .064) and religious affiliation (F = 9.41, p<.05, Æžp2 = .038) were also found to have significant main effects and interaction effects (F = 40.85, p<.01, Æžp2 = .045) on respondents' suicidal ideation. The study concluded that depression, age and religious affiliation influenced suicidal ideation among college students.